White Paper on the Progress, Accomplishments and Future of Sustainable Inland Water Transport - United Nations Economic Commission for Europe (United Nations, 2020)
This is the third edition of a policy paper on the current situation, trends and challenges in Inland Water Transport on European inland waterways of international importance in the region of the Economic Commission for Europe. The White Paper describes the current status of the E Waterway Network, the evolution of the institutional and regulatory framework for inland navigation since 2011, recent programmes and activities of UNECE, the European Union and other international organizations. The White Paper identifies eight priority areas to make IWT in the ECE region more sustainable and competitive, and comes up with policy recommendations for UNECE actions for each of them.